PERFIL METABOLÔMICO SÉRICO DE PACIENTES NA FASE AGUDA DE CHIKUNGUNYA - Camila Amato Montalbano (2022)
Chikungunya is an RNA arbovirus causes long-lasting debilitating arthralgia. This study aimed to identify the serum metabolomic profile of patients during the acute phase of the disease. For that, 25 individuals with clinical and laboratory diagnosis for CHIKV (CHIKV+ Group) were included in the study. In addition, 19 suspected subjects with negative laboratory results for CHIKV (CHIKV-Group) and 15 healthy subjects (Control Group) were included in the study. Patients in the CHIKV+ Group and the CHIKV- Group were evaluated at two moments: Phase M0 (1 to 10 days of symptoms) and Phase M1 (11 to 22 days of symptoms). These patients were further divided into four subgroups, according to the arthralgia intensity and whether they reached chronicity or not: Hight Severity (HS) subgroup, Mild to Moderate Severity (MMS) subgroup, Chronic (C) subgroup and Non chronic subgroup (NC). Serum samples were submitted to purification with methanol and then to High Performance Liquid Chromatography hyphenated with a Mass Spectrometer (CLAEM/MS). Finally, the compounds were identified, and the findings were biologically interpreted using appropriate tools. Results revealed 12 lipid compounds downregulated during M0 in CHIKV+ compared to CHIKV- and CG, many of which are involved in the formation of cell membranes, which are important for each part of the flavivirus and togavirus life cycles, including input, replication, mount, and output. Therefore, CHIKV uses these lipids too much inside the cells, with depletion in the serum. Ten of these lipids keep their levels reduced in M1, demonstrating that the virus continues to use lipids in favor of its perpetuation. The 17-phenyl trinor PGF2α-AS is a pain biomarker of the initial moment of acute and chronic phase. Down-regulation of the Gln Arg Phe compound was identified as a biomarker of chronicity. The discovery of these metabolic changes can lead to the elucidation of factors of the pathophysiology of the disease, being useful for a better understanding of it, which can improve the management of patients, offering them a better quality of life during treatment and avoiding the subsequent stages of this disease. Keywords: chikungunya, acute phase, metabolomic analysis.